2010
DOI: 10.1051/0004-6361/201015440
|View full text |Cite
|
Sign up to set email alerts
|

The universal red-giant oscillation pattern

Abstract: Aims. The CoRoT and Kepler satellites have provided thousands of red-giant oscillation spectra. The analysis of these spectra requires efficient methods of identifying all eigenmode parameters. Methods. The assumption of new scaling laws allowed us to construct a theoretical oscillation pattern. We then obtained a highly precise determination of the large separation by correlating the observed patterns with this reference. Results. We demonstrate that this pattern is universal and are able to unambiguously ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
230
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 171 publications
(243 citation statements)
references
References 26 publications
(37 reference statements)
13
230
0
Order By: Relevance
“…This curvature, always with the same concavity sign, is particularly visible in red giant oscillations (e.g., Mosser et al 2011;Kallinger et al 2012), which show solar-like oscillations at low radial order (e.g., De Ridder et al 2009;Bedding et al 2010a). Figure 1 shows a typical example of the non-negligible curvature in the échelle diagram of a main-sequence star with many radial orders.…”
Section: The Asymptotic Expansion Used In Practicementioning
confidence: 89%
“…This curvature, always with the same concavity sign, is particularly visible in red giant oscillations (e.g., Mosser et al 2011;Kallinger et al 2012), which show solar-like oscillations at low radial order (e.g., De Ridder et al 2009;Bedding et al 2010a). Figure 1 shows a typical example of the non-negligible curvature in the échelle diagram of a main-sequence star with many radial orders.…”
Section: The Asymptotic Expansion Used In Practicementioning
confidence: 89%
“…Models with a large density contrast show a frequency difference between consecutive modes that is much smaller than for models at the bottom of the RGB or in the He-B phase. These properties have been measured by Bedding et al (2011) in the spectra of red giants observed by Kepler and also in those of CoRoT red giants (Mosser et al, 2011a). At a given ∆ ν (that of the red clump) the difference of period (∆ P) between consecutive modes gathers the stars in two groups: one characterized by targets with ∆ P > 100 s and one with ∆ P < 60 s. The comparison with theoretical computations allows us to identify these two groups with stars that are burning He at the center, for the first group, and with stars that are still burning H in a shell during the ascending RGB for the second one, and then to lift the degeneracy between RGB and He-B models with the same ∆ ν and ν max .…”
Section: Deviation From Asymptotic Approximation: Evolutionary Statementioning
confidence: 95%
“…On the other hand, the sample of red giants observed by CoRoT during the first two runs is dominated by red clump stars (Miglio et al, 2009;Mosser et al, 2010) and the analysis of their oscillation properties by Mosser et al (2011b) showed that all the modes are arranged in almost vertical lines corresponding to different radial orders, and that a large dispersion is found for dipole modes at ∆ ν ∼ 4 µHz, that is the value of the large separation corresponding to the red-clump luminosity. The comparison between these observational results and the theoretical predictions for the same stellar population (Montalbán et al, 2010b) is noteworthy.…”
Section: Deviation From Asymptotic Approximation: Evolutionary Statementioning
confidence: 99%
“…Bedding et al 2011;Mosser et al 2011b). The true period spacing ΔΠ 1 describes the constant period spacing of pure dipole g modes, which cannot be observed directly.…”
Section: Evolutionary Status Of Red Giant Heartbeat Starsmentioning
confidence: 99%
“…Previous analyses (Beck et al 2012;Deheuvels et al 2012;Mosser et al 2012a) only revealed the ratio of the (Mosser et al 2011b) for = 0, 1, 2 and 3 and are indicated with blue, red, green and yellow vertical bars, respectively. The effects of rotation are visible as the splitting of dipole modes, located in the centre of each panel.…”
Section: Testing Of the Rotational Profile From Forward Modellingmentioning
confidence: 99%